A protective Zika virus E-dimer-based subunit vaccine engineered to abrogate antibody-dependent enhancement of dengue infection - Campos, JL; Dejnirattisai, W; Jagger, BW; Lopez-Camacho, C; Wongwiwat, W; Durnell, LA; Winkler, ES; Chen, RE; Reyes-Sandoval, A; Rey, FA; Diamond, MS; Mongkolsapaya, J; et al. (Springer Nature, 2019)
Infections with dengue (DENV) and Zika (ZIKV) viruses can induce cross-reactive antibody responses. Two immunodominant epitopes, to precursor membrane protein (prM) or the fusion loop epitope (FLE) on envelope (E) protein are recognized by cross-reactive antibodies1, 2, 3 that are not only poorly neutralizing, but can also promote increased viral replication and disease seerity via Fc-gamma receptor mediated infection of myeloid cells, a process termed antibody-dependent enhancement (ADE)1, 4, 5 . ADE is a significant concern for both ZIKV and DENV vaccines as the induction of poorly-neutralizing cross-reactive antibodies may prime an individual for ADE upon natural infection. In this report, we describe the design and production of covalently-stabilized ZIKV E-dimers, which lack prM and do not expose the immunodominant FLE. Immunization of mice with ZIKV E-dimers induces dimer-specific antibodies, which protected against ZIKV challenge during pregnancy. Importantly, the ZIKV E-dimer-induced response does not cross-react with DENV or induce ADE of DENV infection.